The Impact of Expectation for Pain Relief on Orofacial Pain Treatment Outcomes - Haviv, Yaron; Mazor, Sigal; Shani, Margolis; Yanko, Robert; Aframian, Doron J.; Zadik, Yehuda; Ben-David, Shiri; Wilensky, Asaf; Sharav, Yair (Frontiers in Psychiatry, 2021)
Aims: To examine the effects of expectations for pain relief on the objective and subjective outcome of chronic orofacial pain (OFP) treatment. Materials and Methods: Sixty individuals referred to the Orofacial Pain Clinic at the Hebrew University-Hadassah School of Dental Medicine between 2015 and 2017 with OFP reported their expectation for pain relief upon initial consultation. They were also interviewed by telephone after treatment and asked to recall their expectations, referred to as “recalled expectations” (RE). Correlations between RE and treatment success were calculated from pain diaries, and from subjective pain improvement rates (PIR) reported by the patients. Results: 21 males (35.0%) and 39 females (65%), mean age of 46.90±15.77 years and mean pain duration of 49.07±51.95 months participated in the study. All participants rated their expectations as "10" on a 0 to 10 scale during their first visit. RE did not correlate with diary ratings, (P=0.773) but inversely correlated (-0.3) with PIR (P=0.020) treatment outcomes. Conclusions: Expectations for pain relief, reported as 10 on a 0-10 scale during the first appointment, may reflect the patient’s desire for complete relief of their pain rather than their expectations. Inverse correlation between recalled expectations and subjective outcome may be due to the nature of recalled expectations when patients already knew their treatment outcomes, and may be explained by the concept of cognitive dissonance.